America's service meltdown : restoring service excellence in the age of the customer - Pupo, Raul (Praeger/ABC-CLIO, 2010)
Readers will discover what it takes to serve customers superbly, how excellent customer service profoundly improves profitability, and how to identify the biggest obstacles to good service. Most importantly, they will be rewarded with concrete instructions that will enable them to deliver top-notch customer service every step of the way.